Analisis Yuridis Terhadap Penggunaan Pay Later di Aplikasi Shopee: Perspektif Mazhab al-Syafi’i - Rahayu, Ayu; Aisyah, Siti (Universitas Islam Negeri Alauddin Makassar, 2023)
In e-commerce there is one part that is in great demand today, namely the marketplace. One of the marketplaces that is in great demand by the Indonesian people, especially is Shopee. Shopee also provides various very interesting features on the Shopee mobile application, one of which is Shopee Pay Later. Credit available on Shopee Pay Later is the application of the qardh contract in Islamic law. The purpose of this study is to find out the features that exist in the Shopee marketplace, to understand the mechanism of using